'They don't meet the stereotypes in the boxes…': Foster carers' and clinicians' views on the utility of psychometric tools in the mental health assessment of looked after children. (July 2019) - Frogley, Catherine; John, Mary; Denton, Ruth; Querstret, Dawn
Looked after children often experience greater mental health challenges than children in the general population. Consequently, there has been a call for greater focus on early preventive interventions and priority access to specialist mental health support for them. Brief mental health screening tools often provide the gateway to services and yet there is a lack of suitable assessment tools available for looked after children. The current study is the first to explore the perspectives of foster carers and clinicians working in Child and Adolescent Mental Health Services (CAMHS) in relation to the use of two brief screening tools: the Strengths and Difficulties Questionnaire (SDQ) and the Brief Assessment Checklists (BACs). Qualitative data were collected via semi-structured telephone interviews and face-to-face focus groups with 13 female foster carers and 19 clinicians working in a CAMHS setting. Thematic analyses generated six themes which were organised into three superordinate ones centred around: (1) relevance to looked after children; (2) using measures to inform care planning; and (3) current problems when using psychometric measures within the looked after children population. Foster carers and clinicians emphasised the need for a comprehensive understanding of these children given the complexity of their difficulties. There was acknowledgement that psychometric measures could facilitate and contribute to this by highlighting difficulties, providing accurate feedback to carers and clinicians, and enabling access to support. However, both groups seldom felt that current measures were nuanced enough to adequately capture the children's needs. Yet screening tools play a crucial role in identifying the mental health needs of looked after children and facilitating access to services. Further research is needed to establish the ability of such measures to increase the sensitivity of their complex needs assessment. A number of clinical recommendations are also discussed in relation to the assessment of mental health in this population.